2005
DOI: 10.1111/j.1745-6592.2005.00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Inexpensive Small‐Diameter Temperature Logger for Documenting Ground Water–River Interactions

Abstract: Increasing numbers of studies are recording detailed temperature data for characterization of ground water–stream exchange. We examined laboratory and field operation of a small‐diameter, stand‐alone and inexpensive temperature logger capable of investigating stream–ground water exchange was examined. The Thermochron iButton is a 17.35‐mm‐diameter by 6‐mm‐thick instrument that costs <$10 when ordered in quantity. Testing of the loggers in a controlled temperature bath revealed a precision of ±0.4°C and an accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 17 publications
3
63
1
Order By: Relevance
“…Calibration improved the accuracy of the iButton data from 61.0uC as reported by the manufacturer (http://www.ibutton.com) to approximately 60.1uC ( fig. 3 of Johnson et al 2005 where Dh is the hydraulic head difference between the piezometer and the surface stream adjacent to the piezometer (m) and Dz is the difference in elevation between the piezometer screen and the streambed surface adjacent to the piezometer (m) ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Calibration improved the accuracy of the iButton data from 61.0uC as reported by the manufacturer (http://www.ibutton.com) to approximately 60.1uC ( fig. 3 of Johnson et al 2005 where Dh is the hydraulic head difference between the piezometer and the surface stream adjacent to the piezometer (m) and Dz is the difference in elevation between the piezometer screen and the streambed surface adjacent to the piezometer (m) ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Vertical temperature profiles (TPs) were constructed by embedding seven iButton temperature sensors and loggers (DS1922L, Maxim, Inc., 0.0625 C resolution, 0.5 C accuracy, 130 s response time) [Hubbart et al, 2005;Johnson et al, 2005] into 2.5 cm diameter steel rods at depths of 5, 10, 15, 20, 25, and 30 cm in the streambed and at 5 cm above the streambed. Silicone sealant was used to waterproof the sensors and insulate them from the rod.…”
Section: Field and Laboratory Methodsmentioning
confidence: 99%
“…From these data, a correction factor (either positive or negative) was established for each logger and added to the field results recorded by that logger. More extensive calibration tests by Johnson et al [2005] showed that expected error in similarly calibrated temperature measurements among loggers was <0.25°C.…”
Section: Monitoring Water Temperature Cyclesmentioning
confidence: 99%